Culture Shock Mahasiswa Indonesia dalam Studi di Luar Negeri - Adinda Annisa Zahra; Tia Muthiah Umar (Bandung Conference Series: Public Relations, 2024)
Abstract. As we already know, Culture Shock is something that can be said to be a habit when going through a process of cultural adaptation to a new environment, one of which is abroad. In accordance with the research that I will research, it is entitled "Culture Shock for Indonesian Students in Studying Abroad (Phenomenological Study of Indonesian Students in Perth, Australia)". The aim of this research is to find out what preparations, processes, obstacles and solutions Indonesian students face when adapting so that culture shock can occur. The researcher intends to examine in more depth how Indonesian students deal with Culture Shock. This research uses qualitative research with a phenomenological study approach, constructivism paradigm, and data collection by observation, interviews, and documentation. The results of this research show that each migrant student has their own way of adapting. In the process of cultural adaptation, opening themselves to the surrounding environment, following the existing norms of Perth society. Furthermore, this research uses source triangulation as a technique for testing the validity of the data. This research describes the Culture Shock experienced by Indonesian students abroad, specifically in Perth, Australia. In the process of cultural adaptation, Indonesian students will certainly encounter cultural differences. By going through a process that is appropriate to cultural adaptation, each student will feel comfortable in their new environment. When adapting to culture, every student will definitely experience culture shock and obstacles when facing the cultural adaptation process. Environmental factors can influence the student's adaptation process. Language differences are usually still a major obstacle when students are in the process of adjusting to a new culture. Abstrak. Seperti yang sudah kita ketahui Culture Shock adalah hal yang dapat di katakan sebagai kebiasaan saat sedang melalui proses adaptasi budaya dengan lingkungan baru salah satunya di Luar Negeri. Sesuai dengan penelitian yang akan saya teliti ini berjudul “Culture Shock Mahasiswa Indonesia dalam studi di luar negeri (Studi Fenomenologi pada mahasiswa indonesia di Perth Australia)”. Tujuan penelitian ini adalah untuk mengetahui persiapan, proses, hambatan dan solusi apa yang di hadapai oleh mahasiswa Indonesia saat ber-adaptasi sehingga dapat terjadinya culture shock. Peneliti bermaksud untuk mengkaji lebih dalam akan bagaimana mahasiswa Indonesia dalam menghadapi Culture Shock. Penelitian ini menggunakan penelitian kuliatatif dengan pendekatan studi fenomenologi, paradigma konstruktivisme, serta pengumpulan data dengan observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukan bahwa setiap mahasiswa pendatang memiliki caranya masing-masing saat melakukan adaptasi Dalam proses adaptasi budaya, membuka diri dengan lingkungan sekitar, mengikuti norma yang ada dengan masyarakat Perth.Selanjutnya penelitian ini menggunakan tringgulasi sumber sebagai Teknik uji keabsahan data. Penelitian ini memaparkan Culture Shock yang dialami oleh mahasiswa Indonesia di luar Negeri tepatnya di Perth Australia. Dalam proses adaptasi budaya, mahasiswa Indonesia tentu akan menemukan perbedaan-perbedaan budaya. Dengan melewati proses yang sesuai dengan adaptasi budaya, nantinya setiap mahasiswa akan merasakan kenyamanan terhadap lingkungan barunya. Saat melakukan adaptasi budaya, setiap mahasiswa pasti memiliki culture shock dan hambatan ketika sedang menghadapi proses adaptasi budaya tersebut. Faktor lingkungan bisa mempengaruhi proses adaptasi pada mahasiswa tersebut. Perbedaan bahasa biasanya masih menjadi kendala utama ketika mahasiswa sedang melakukan proses penyesuian dengan budaya baru.